Internet of Things Driven Smart Cities in Post Pandemic Era - Rahimunnisa, K. (IRO Journal on Sustainable Wireless Systems, 2022)
The rise of the Internet of Things (IoT) driven smart cities is progressively revolutionizing different aspects of human life, including transportation, communication, health, automotive and security. Several IoT initiatives and experimental setting have been proposed in recent years to establish digital and smart infrastructures. Despite the hype, the COVID-19 pandemic still has an impact on many aspects of urban life, raising concerns about the viability of past and contemporary patterns of urban design and growth. The COVID-19 epidemic has significantly altered everyday lives, damaged the economy of several countries, affected global economic goals, and so on. In such cases, it is highly required to initiate a research discussion on the influence of COVID-19 in smart cities. Several researchers and policymakers have previously recognized the need for improved smart city infrastructure. This research study reviews the multiple research discussions that design and develop new urban planning and smart city design paradigms and models in the post-COVID period that reflect the insights gained from the pandemic. The study also discussed how smart cities innovation, operations, and preventive maintenance will be influenced after COVID-19. Finally, the proposed study concluded that the smarter cities equipped with IoT driven technologies will be able to prevent pandemics in the near future.